Chaetozone and Caulleriella (Polychaeta: Cirratulidae) from the Pacific Coast of Costa Rica, with description of eight new species - Dean, Harlan K.; Blake, James A. (Zootaxa, 2007)
Polychaetes of the family Cirratulidae have often been poorly understood yet are very common and important components of intertidal and subtidal benthic communities. Five species of Chaetozone are here described from the Pacific coast of Costa Rica. Three of these species, C. acuminata sp. nov., C. cimar sp. nov., and C. nicoyana sp. nov., are new to science while C. corona Berkeley & Berkeley, 1941 and C. hedgpethi Blake, 1996 were previously described from California. C. acuminata sp. nov. has an elongate peristomium, a narrow anterior body region and elongate unidentate spines; the upper notosetal and lower neurosetal spines may be bidentate. C. cimar sp. nov. has notopodial and neuropodial spines in the mid-body region and partially complete posterior cinctures. C. nicoyana sp. nov. has a double row of posterior notopodial spines with fine recurved tips. Five new species in the genus Caulleriella are also described: C. cucula sp. nov., C. dulcei sp. nov., C. minuta sp. nov., C. moralesensis sp. nov., and C. murilloi sp. nov. C. cucula sp. nov. has dark, prominent nuchal organs, notopodial spines from the midbody to the posterior body region, capillary setae accompanying the spines in posterior setigers, bidentate neuropodial spines throughout. C. dulcei sp. nov. has accompanying capillary setae in all parapodial lobes except the posterior neuropodia, and notopodial spines from the anterior to mid-body region. C. minuta sp. nov. is a very small species with neuropodial spines beginning at setiger 4, capillaries accompanying the spines in posterior notopodia and segment 1 fused with setiger 1. C. moralesensis sp. nov. has notopodial spines from the anterior region and capillaries accompanying spines in both the notopodia and neuropodia. C. murilloi sp. nov. has dorsal tentacles emerging from setiger 3 and highly modified bidentate spines with low, rounded teeth or an encircling hood. Morphological characters which best aid in the differentiation of species in each genus are discussed including the use of peristomial annulations as a morphological character.